Direct Effects of Riluzole on 5-Hydroxytryptamine (5-HT)3 Receptor-Activated Ion Currents in NCB-20 Neuroblastoma Cells - Ki Jung Kim; Hyeong Seok Cho; Se Joon Choi; Seung Hyun Jeun; Seong Yun Kim; Ki-Wug Sung (Elsevier, 2008)
The pharmacological action of riluzole, a drug that has been approved as a neuroprotective agent for the treatment of amyotrophic lateral sclerosis, has not yet been established. We examined the effects of riluzole on 5-hydroxytryptamine (5-HT)3 receptors in NCB-20 neuroblastoma cells using the whole-cell voltage clamp technique combined with a fast drug application method. Co-application of riluzole (1 - 300 μM, 5 s) produced a dose-dependent reduction in peak amplitudes and in the rise slope of the currents induced by 2 μM 5-HT. In addition, 5-HT3-mediated currents evoked by dopamine, a partial 5-HT3-receptor agonist, were inhibited by riluzole co-application. These inhibitory effects were clearly shown at low concentrations of 5-HT. The decay time constants of the receptor desensitization and deactivation were also significantly attenuated by riluzole. G-protein inhibitors (pertussis toxin and guanosine 5'-[β-thio] diphosphate) did not completely block these inhibitory actions of riluzole. These results indicate that riluzole inhibits 5-HT3-induced ion currents directly by slowing channel activation in NCB-20 neuroblastoma cells. Keywords:: riluzole, 5-HT3 receptor, ion channel, patch clamp, NCB-20 cell